Polymer-silicate composite based on alternative raw materials under conditions of increased temperature - Melichar, Tomáš; Bydžovský, Jiří (Elsevier, 2016)
The paper presents research into studying the properties of composite materials with polymer-silicate matrix and porous (lightweight) filler. Specifically, the matrix based on cement substituted by 35% of alternative raw material was considered. In case of filler aggregate based sintered ash was used. Investigated materials were exposed at high temperatures. Thermal loading took place gradually in temperature increments of 22 °C (reference conditions), 400, 600, 800 and 1000 °C with subsequent controlled cooling. Attention was also focused on various ways of cooling – slow in the furnace (1 °C/min) and immersion in water (bath temperature c. 18 °C). Suitability of matrix modification and use of porous fillers based on alternative raw materials was proved by set of analyses. After exposure in an environment with a temperature of 1000 °C followed by quench cooling was set residual compressive strength of about 40%, which is relatively high for this type of the matrix. The curves of residual strength with different types of cooling are intriguing too. Selected samples were also investigated by using micro/structural techniques, where the emphasis was placed on the formation of any defects related.

The paper presents research into studying the properties of composite materials with polymer-silicate matrix and porous (lightweight) filler. Specifically, the matrix based on cement substituted by 35% of alternative raw material was considered. In case of filler aggregate based sintered ash was used. Investigated materials were exposed at high temperatures. Thermal loading took place gradually in temperature increments of 22 °C (reference conditions), 400, 600, 800 and 1000 °C with subsequent controlled cooling. Attention was also focused on various ways of cooling – slow in the furnace (1 °C/min) and immersion in water (bath temperature c. 18 °C). Suitability of matrix modification and use of porous fillers based on alternative raw materials was proved by set of analyses. After exposure in an environment with a temperature of 1000 °C followed by quench cooling was set residual compressive strength of about 40%, which is relatively high for this type of the matrix. The curves of residual strength with different types of cooling are intriguing too. Selected samples were also investigated by using micro/structural techniques, where the emphasis was placed on the formation of any defects related.
Polymer-silicate composite based on alternative raw materials under conditions of increased temperature
Keywords: Composite; extreme; temperature; regime; cooling.; Composite; extreme; temperature; regime; cooling.